Carbon / bimetallic selenide composite microsphere material, preparation method and application
By growing metal selenide inside the hollow carbon microspheres to form carbon/bimetal selenide composite microsphere materials, the problem of large volume changes in transition metal selenide in electrochemical reactions is solved, its cycle life and conductivity are improved, and a high-performance sodium ion battery negative electrode material is achieved.
Patent Information
- Application Number
- CN202411592324.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing transition metal selenide materials are prone to large volume changes during electrochemical reactions and have poor cycle life, which limits their application in sodium ion batteries.
Using the preparation method of carbon/bimetal selenide composite microsphere material, hollow carbon microspheres with hollow structures are prepared by the template method by using the template method, and metal selenide is grown inside them, thereby forming carbon/metal selenide composite microspheres.
The volume expansion of metal selenide is alleviated through the nanostructure, and its circulation life is improved. The composite structure of carbon and metal selenide is enhanced to enhance the conductivity, and a new material with high specific capacity, good rate performance and long cycle life is obtained.
Smart Images

Figure CN119601615A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of methods for preparing negative electrode materials for sodium ion batteries, and specifically relates to a carbon / bimetallic selenide composite microsphere material; and also relates to a method for preparing the carbon / bimetallic selenide composite microsphere material. Background Art
[0002] Due to the limited resources and high cost of lithium, sodium-ion batteries have attracted great interest in recent years as an effective alternative to lithium-ion batteries. Although sodium-ion batteries have made substantial progress recently, the development of negative electrode materials with sufficiently high capacity, long life and low redox potential remains a major challenge facing the scientific community. In addition, the ion size of sodium is larger than that of lithium ions, so the negative electrode materials of sodium-ion batteries should generally have a suitable crystal structure and larger interlayer channels than those of lithium-ion battery negative electrode materials. Graphite, Li4Ti5O 12 Silicon and silicon are the most commonly used and efficient anode materials for lithium-ion batteries, but when used in sodium-ion batteries, these electrode materials produce serious problems, such as slow sodium-ion diffusion rate and significant volume change. Therefore, the rational design and precise exploration of new electrode materials are crucial to achieve high-performance sodium-ion batteries.
[0003] Among many candidate materials, metal selenides have higher volume capacity and rate performance as sodium ion battery electrode materials due to their higher conductivity and higher density compared to metal oxides and sulfides. In addition, metal selenides have a band gap comparable to that of metal selenides and good conductivity. For example, patent 202410425216.6 reports a metal selenide material containing multiple heterogeneous interfaces and its preparation method and application, the process mainly comprising stirring, centrifuging, and selenizing a pre-synthesized ZIF-8 with a mixed solution containing a cobalt source and a ligand at room temperature to obtain a metal selenide. Patent CN202210964911.0 discloses a selenide negative electrode material for sodium ion batteries and a preparation method thereof, wherein germanium powder and selenium powder are reacted at high temperature under vacuum conditions to generate a selenium germanium precursor, and then the obtained selenium germanium precursor is carbonized under an inert atmosphere to obtain a selenide negative electrode material. The above materials are all used for the negative electrode of sodium ion batteries and exhibit certain sodium storage properties. However, transition metal selenides are prone to large volume changes during electrochemical reactions and have poor cycle life, which hinders their practical application.
[0004] Therefore, how to design and alleviate the volume expansion of metal selenides and improve their cycle life is a key issue that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a carbon / bimetallic selenide composite microsphere material, which solves the problem that the existing transition metal selenide materials are prone to large volume changes during electrochemical reactions and have poor cycle life.
[0006] The technical solution adopted by the present invention is a method for preparing a carbon / bimetallic selenide composite microsphere material, and the specific operation steps are as follows: Step 1, mixing the hollow carbon microspheres and the organic ligands uniformly, and then reacting them at high temperature for a certain period of time, then washing the product with ethanol, and drying it to obtain an organic ligand / hollow carbon microsphere composite; Step 2, dispersing the organic ligand / hollow carbon microsphere composite in an organic solvent, then adding a metal salt, mixing and stirring for a certain period of time, centrifuging and drying, to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3, placing the metal organic ligand / hollow carbon microsphere composite material and the selenium source together in a tubular furnace, and performing high-temperature carbonization under the protection of an inert atmosphere to obtain a carbon / bimetallic selenide composite microsphere material.
[0007] The present invention is also characterized in that: Furthermore, in step 1, the organic ligand includes one or more of 4,4'-bipyridine, dimethylimidazole, 2,6-naphthalene dicarboxylic acid, trimeric acid, and thioglycolic acid.
[0008] Furthermore, in step 1, the preparation method of hollow carbon microspheres is as follows: Resorcinol and formaldehyde are added to a mixed solution of deionized water, ethanol and ammonia water; subsequently, silica nanospheres are added to the above solution and stirred for 12 to 36 hours; the solution is transferred to a hydrothermal autoclave and maintained at 80 to 160°C for 8 to 48 hours, and then calcined at 500 to 1000°C for 2 to 6 hours under an inert atmosphere; finally, the material is reacted in hydrofluoric acid to remove silica to obtain phenolic resin-based hollow carbon microspheres; The ratio of resorcinol to formaldehyde is 0.1~1g:0.1~2mL.
[0009] Furthermore, in step 1, the mass ratio of the hollow carbon microspheres to the organic ligand is 1:1-15, the reaction temperature is 100-160°C, and the reaction time is 8-36h.
[0010] Furthermore, in step 2, the organic solvent is one or more of isopropanol, N,N-dimethylformamide, ethanol, and methanol.
[0011] Furthermore, in step 2, the metal salt is any one of zinc salt, cobalt salt, iron salt, manganese salt, nickel salt, and copper salt, or a combination of at least two thereof; and the mass ratio of the organic ligand / hollow carbon microsphere complex to the metal salt is 1:0.5~5.
[0012] Furthermore, in step 2, the mixing reaction time of the organic ligand / hollow carbon microsphere complex and the metal salt is 1 to 12 hours.
[0013] Furthermore, in step 3, the mass ratio of the metal organic ligand / hollow carbon microsphere composite material to the selenium source is 1:1-5; the selenium source is one or more of selenium powder, dimethyl selenium, and selenourea.
[0014] Furthermore, in step 3, the heating rate of the high temperature carbonization is 2-10°C / min, the calcination time is 1-5h, and the constant temperature is 400-700°C.
[0015] The second technical solution adopted by the present invention is: a carbon / bimetallic selenide composite microsphere material prepared by a preparation method of a carbon / bimetallic selenide composite microsphere material; the carbon / bimetallic selenide composite microsphere material can be used as a negative electrode material in a sodium ion battery.
[0016] The beneficial effects of the present invention are: The present invention uses nano-silica microspheres as templates and phenolic resin as a carbon source, and prepares hollow carbon microspheres with a hollow structure by a template method, and then uses the hollow carbon microspheres as nanoreactors to grow metal selenides inside them, thereby obtaining carbon / metal selenide composite microspheres. Since the internal space of the hollow carbon microspheres is limited, the growth size of the metal selenide is limited, and thus it tends to be nano-sized. The nano-sized structure helps to alleviate the volume expansion of the metal selenide, and at the same time exposes more active sites, which is conducive to the reaction of sodium ions with it, thereby increasing the specific capacity of the metal selenide. Further, the hollow carbon microspheres can expand the electrochemical reaction interface and inhibit the volume expansion of the metal selenide, thereby increasing the theoretical capacity of the metal selenide and enhancing its cycle stability. In addition, the construction of carbon and metal selenide composite materials can combine the advantages of the two, enhance the conductivity of the metal selenide, and finally obtain a new type of carbon / metal selenide composite microsphere material with high specific capacity, good rate performance, and long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the SEM image of C / NiSe2 / CoSe2 prepared in Example 1 of the present invention.
[0018] Figure 2 XRD diagrams of C / NiSe2 / CoSe2 prepared in Example 1 of the present invention, C / NiSe2 prepared in Comparative Example 1, and C / CoSe2 prepared in Comparative Example 2.
[0019] Figure 3 The cycle performance curves of C / NiSe2 / CoSe2 prepared in Example 1 of the present invention, C / NiSe2 prepared in Comparative Example 1, and C / CoSe2 prepared in Comparative Example 2.
[0020] Figure 4 The rate performance curves of C / NiSe2 / CoSe2 prepared in Example 1 of the present invention, C / NiSe2 prepared in Comparative Example 1, and C / CoSe2 prepared in Comparative Example 2. DETAILED DESCRIPTION
[0021] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0022] Example 1 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: Mix hollow carbon microspheres and dimethylimidazole in a mass ratio of 1:10, put them into a hydrothermal autoclave and heat them at 140°C for 24 hours, then wash the product with ethanol to remove the organic ligands that have not penetrated into the hollow carbon microspheres, and obtain an organic ligand / hollow carbon microsphere composite after drying; Step 2: Disperse the organic ligand / hollow carbon microsphere composite in 10mL of methanol solution, then add nickel chloride and cobalt chloride, the mass ratio of the organic ligand / hollow carbon microsphere composite, nickel chloride and cobalt chloride is 1:0.5:0.5, stir the reaction for 5 hours, centrifuge and dry the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:2, heat to 500°C at a heating rate of 5°C / min under argon atmosphere, and calcine for 1h to obtain a carbon / nickel selenide / cobalt selenide composite microsphere material, recorded as C / NiSe2 / CoSe2.
[0023] Example 2 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and dimethylimidazole are mixed in a mass ratio of 1:10, placed in a hydrothermal autoclave and heated at 160°C for 14 hours, and then the product is washed with ethanol to remove the organic ligand dimethylimidazole that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding zinc chloride and copper chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, zinc chloride and copper chloride is 1:1:1, stirring the reaction for 5 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:1, heat to 600°C at a heating rate of 5°C / min under argon atmosphere, and calcine for 2h to obtain a carbon / zinc selenide / copper selenide composite microsphere material, recorded as C / ZnSe2 / CuSe2.
[0024] Example 3 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and dimethylimidazole are mixed in a mass ratio of 1:5, placed in a hydrothermal autoclave and heated at 160°C for 10 hours, then the product is washed with ethanol to remove the organic ligand dimethylimidazole that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding nickel chloride and manganese chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and manganese chloride is 1:2:2, stirring the reaction for 5 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:1, heat to 500°C at a heating rate of 3°C / min under argon atmosphere, and calcine for 3 hours to obtain a carbon / nickel selenide / manganese selenide composite microsphere material, recorded as C / NiSe2 / MnSe2.
[0025] Example 4 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and dimethylimidazole were mixed in a mass ratio of 1:8, placed in a hydrothermal autoclave and heated at 145°C for 24 hours, then the product was washed with ethanol to remove the organic ligands that did not penetrate into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: Disperse the organic ligand / hollow carbon microsphere complex in 20 mL of methanol solution, then add nickel chloride and copper chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and copper chloride is 1:1:1, stir and react for 12 hours, centrifuge and dry the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenourea in a mass ratio of 1:3, heat to 600°C at a heating rate of 10°C / min under argon atmosphere, and calcine for 5h to obtain a carbon / nickel selenide / copper selenide composite microsphere material, recorded as C / NiSe2 / CuSe2.
[0026] Example 5 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and dimethylimidazole were mixed in a mass ratio of 1:8, placed in a hydrothermal autoclave and heated at 145°C for 24 hours, then the product was washed with ethanol to remove the organic ligands that did not penetrate into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: Disperse the organic ligand / hollow carbon microsphere complex in 20 mL of methanol solution, then add nickel chloride and manganese chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and manganese chloride is 1:0.5:1, stir and react for 12 hours, centrifuge and dry the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:3, heat to 600°C at a heating rate of 10°C / min under argon atmosphere, and calcine for 5 hours to obtain a carbon / nickel selenide / manganese selenide composite microsphere material, recorded as C / NiSe2 / MnSe2.
[0027] Example 6 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and 4,4'-bipyridine are mixed in a mass ratio of 1:13, placed in a hydrothermal autoclave and heated at 120°C for 30 hours, then the product is washed with ethanol to remove the organic ligands that have not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding nickel chloride and copper chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and copper chloride is 1:0.5:1, stirring the reaction for 7 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and dimethyl selenide in a mass ratio of 1:4, heat to 600°C at a heating rate of 10°C / min under argon atmosphere, and calcine for 5 hours to obtain a carbon / nickel selenide / copper selenide composite microsphere material, recorded as C / NiSe2 / CuSe2.
[0028] Example 7 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and 2,6-naphthalene dicarboxylic acid are mixed in a mass ratio of 1:7, placed in a hydrothermal autoclave and heated at 100°C for 28 hours, then the product is washed with ethanol to remove the organic ligand that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding ferric chloride and nickel chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, ferric chloride and nickel chloride is 1:1:2, stirring the reaction for 5 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:2.5, heat to 600°C at a heating rate of 8°C / min under argon atmosphere, and calcine for 2h to obtain a carbon / iron selenide / nickel selenide composite microsphere material, denoted as C / FeSe2 / NiSe2.
[0029] Example 8 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and terephthalic acid are mixed in a mass ratio of 1:8, placed in a hydrothermal autoclave and heated at 145°C for 24 hours, then the product is washed with ethanol to remove the organic ligands that have not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding nickel chloride and copper chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and copper chloride is 1:2:1, stirring and mixing for 6 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenourea in a mass ratio of 1:2, heat to 450°C at a heating rate of 5°C / min under argon atmosphere, and calcine for 5h to obtain a carbon / nickel selenide / copper selenide composite microsphere material, denoted as C / NiSe2 / CuSe2.
[0030] Example 9 The preparation method of the carbon / bimetallic selenide composite microsphere material of the present invention has the following specific operating steps: Step 1: hollow carbon microspheres and thioglycolic acid are mixed in a mass ratio of 1:12, placed in a hydrothermal autoclave and heated at 130°C for 32 hours, then the product is washed with ethanol to remove the organic ligand that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding nickel chloride and cobalt chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex, nickel chloride and cobalt chloride is 1:1.5:2, stirring the reaction for 10 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and dimethyl selenide in a mass ratio of 1:4, heat to 600°C at a heating rate of 4°C / min under argon atmosphere, and calcine for 4 hours to obtain a carbon / nickel selenide / cobalt selenide composite microsphere material, recorded as C / NiSe2 / CoSe2.
[0031] The hollow carbon microspheres used in Examples 1-9 of the present invention can be purchased on the market or prepared by oneself. The method for preparing the hollow carbon microspheres by oneself is as follows: Resorcinol and formaldehyde are added to a mixed solution of deionized water, ethanol and ammonia water; subsequently, silica nanospheres are added to the above solution and stirred for 12 to 36 hours; the solution is transferred to a hydrothermal autoclave and maintained at 80 to 160°C for 8 to 48 hours, and then calcined at 500 to 1000°C for 2 to 6 hours under an inert atmosphere; finally, the material is reacted in hydrofluoric acid to remove silica to obtain phenolic resin-based hollow carbon microspheres; Among them, the ratio of resorcinol to formaldehyde is 0.1~1g:0.1~2mL.
[0032] Comparative Example 1 Step 1: hollow carbon microspheres and organic ligand dimethylimidazole are mixed in a mass ratio of 1:10, placed in a hydrothermal autoclave and heated at 140°C for 24 hours, then the product is washed with ethanol to remove the organic ligand that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding nickel chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex to nickel chloride is 1:1, stirring the reaction for 5 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:2, heat to 500°C at a heating rate of 5°C / min under argon atmosphere, and calcine for 1h to obtain a carbon / nickel selenide composite microsphere material, recorded as C / NiSe2.
[0033] In this comparative example, a single metal salt, nickel chloride, was added.
[0034] Comparative Example 2 Step 1: hollow carbon microspheres and organic ligand dimethylimidazole are mixed in a mass ratio of 1:10, placed in a hydrothermal autoclave and heated at 140°C for 24 hours, then the product is washed with ethanol to remove the organic ligand that has not penetrated into the hollow carbon microspheres, and then dried to obtain an organic ligand / hollow carbon microsphere composite; Step 2: dispersing the organic ligand / hollow carbon microsphere complex in a methanol solution, and then adding cobalt chloride, the mass ratio of the organic ligand / hollow carbon microsphere complex and cobalt chloride is 1:1, stirring the reaction for 5 hours, centrifuging and drying the reaction product to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3: Mix the metal organic ligand / hollow carbon microsphere composite material and selenium powder in a mass ratio of 1:2, heat to 500°C at a heating rate of 5°C / min under argon atmosphere, and calcine for 1h to obtain a carbon / cobalt selenide composite microsphere material, denoted as C / CoSe2.
[0035] In this comparative example, a single metal salt, cobalt chloride, was added.
[0036] Figure 1 This is a scanning electron microscope image of the carbon / bimetallic selenide composite microsphere material C / NiSe2 / CoSe2 obtained in Example 1. It can be seen that the metal selenide grows on the hollow carbon microspheres as a substrate to form a uniform composite material structure.
[0037] Figure 2 The XRD patterns of the carbon / bimetallic selenide composite microsphere material C / NiSe2 / CoSe2 prepared in Example 1 of the present invention, C / NiSe2 prepared in Comparative Example 1, and C / CoSe2 prepared in Comparative Example 2 show diffraction peaks corresponding to carbon and selenide, and do not contain other impurities, indicating effective synthesis of the composite material.
[0038] The samples obtained in Example 1, Comparative Example 1 and Comparative Example 2 were mixed with PVDF and conductive carbon black in a ratio of 7:1:2 to prepare electrodes, and metallic sodium was used as the counter electrode. The button cells were assembled and their cycle performance was tested. Figure 3 As shown, at a current density of 0.1 A / g, the reversible capacities of C / NiSe2 / CoSe2, C / NiSe2 and C / CoSe2 can be maintained at 431, 357 and 221 mAh / g after 100 cycles. Figure 4 The rate performance curves of the carbon / cobalt selenide composite microsphere materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention show that the reversible capacities of the sample obtained in Example 1 are 539, 463, 398, 364, 331, 302, 284 and 232 mAh / g at 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, 1 and 2 A / g, respectively. It can be found that at different current densities, they are all better than Comparative Example 1 and Comparative Example 2.
[0039] It can be seen that the method provided by the present invention can effectively alleviate the problems of unstable structure, large volume expansion and poor cycle performance of single metal selenide. The excellent sodium storage performance of carbon / metal selenide composite microspheres is mainly attributed to the following points: (1) Hollow carbon microspheres as carbon substrates can enhance the overall electronic conductivity of the material. At the same time, they can use their limited space to inhibit the volume expansion of selenide during the electrochemical reaction and improve the cycle performance of the composite material. (2) Due to the limited growth space of metal selenides, the resulting structure tends to be nanosized, thereby exposing more active sites, which is conducive to the reaction of sodium ions with them to produce higher capacity; (3) The carbon / bimetallic selenide composite microsphere material of the present invention has a built-in electric field in the heterostructure interface, which can reduce the activation energy barrier and promote the reaction kinetics due to lattice distortion and electron rearrangement. At the same time, the heterostructure can accelerate charge transfer, improve sodium ion storage, and avoid structural damage caused by sodium ion insertion / extraction, thereby improving the cycle performance of the material.
[0040] The synthesis principle of the carbon / bimetallic selenide composite microsphere material of the present invention is as follows: The present invention prepares carbon / metal selenide composite microsphere materials by means of the structural confinement of hollow carbon microspheres. Firstly, based on the capillary force of hollow carbon microspheres, organic ligands are infiltrated into the microspheres by means of a melt diffusion strategy, and then react with metal cations in an organic solvent to anchor the metal organic framework on the surface of the hollow carbon microspheres, so that after selenization, a carbon / metal selenide microsphere material based on the hollow carbon microspheres can be formed.
[0041] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a carbon / bimetallic selenide composite microsphere material, characterized in that: The specific steps are as follows: Step 1, mixing the hollow carbon microspheres and the organic ligands uniformly, and then reacting them at high temperature for a certain period of time, then washing the product with ethanol, and drying it to obtain an organic ligand / hollow carbon microsphere composite; Step 2, dispersing the organic ligand / hollow carbon microsphere composite in an organic solvent, then adding a metal salt, mixing and stirring for a certain period of time, centrifuging and drying, to obtain a metal organic ligand / hollow carbon microsphere composite material; Step 3, placing the metal organic ligand / hollow carbon microsphere composite material and the selenium source together in a tubular furnace, and performing high-temperature carbonization under the protection of an inert atmosphere to obtain a carbon / bimetallic selenide composite microsphere material.
2. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 1, the organic ligand includes one or more of 4,4'-bipyridine, dimethylimidazole, 2,6-naphthalene dicarboxylic acid, trimeric acid, and thioglycolic acid.
3. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 1, the preparation method of hollow carbon microspheres is as follows: Resorcinol and formaldehyde are added to a mixed solution of deionized water, ethanol and ammonia water; subsequently, silica nanospheres are added to the above solution and stirred for 12 to 36 hours; the solution is transferred to a hydrothermal autoclave and maintained at 80 to 160°C for 8 to 48 hours, and then calcined at 500 to 1000°C for 2 to 6 hours under an inert atmosphere; finally, the material is reacted in hydrofluoric acid to remove silica to obtain phenolic resin-based hollow carbon microspheres; The ratio of resorcinol to formaldehyde is 0.1~1g:0.1~2mL.
4. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 1, the mass ratio of the hollow carbon microspheres to the organic ligand is 1:1-15, the reaction temperature is 100-160°C, and the reaction time is 8-36h.
5. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 2, the organic solvent is one or more of isopropanol, N,N-dimethylformamide, ethanol, and methanol; The metal salt is any one of zinc salt, cobalt salt, iron salt, manganese salt, nickel salt and copper salt, or a combination of at least two of them; the mass ratio of the organic ligand / hollow carbon microsphere composite to the metal salt is 1:0.5-5.
6. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 2, the mixing reaction time of the organic ligand / hollow carbon microsphere complex and the metal salt is 1 to 12 hours.
7. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 3, the mass ratio of the metal organic ligand / hollow carbon microsphere composite material to the selenium source is 1:1-5; the selenium source is one or more of selenium powder, dimethyl selenium, and selenourea.
8. The method for preparing the carbon / bimetallic selenide composite microsphere material according to claim 1, characterized in that: In step 3, the heating rate of the high-temperature carbonization is 2-10°C / min, the calcination time is 1-5h, and the constant temperature is 400-700°C.
9. A carbon / bimetallic selenide composite microsphere material prepared according to the method for preparing a carbon / bimetallic selenide composite microsphere material according to any one of claims 1 to 8.
10. Use of the carbon / bimetallic selenide composite microsphere material according to claim 9 in sodium ion batteries.
Citation Information
Patent Citations
A selenide anode material for sodium-ion batteries and its preparation method, sodium-ion batteries
CN115285947B
A metal selenide material containing multiple heterogeneous interfaces and its preparation method and application
CN118004978B
Preparation method of hollow carbon nanospheres with MOFs (metal-organic frameworks) formed through limited-range growth inside
CN107522867A
Imidazole zeolite frame composite nanomaterial and preparation method and application thereof
CN109663573A
Catalyst, and preparation method and application thereof
CN112615014A
Cited By
Preparation method and application of Cu micro-doped CoSe2 positive electrode material of magnesium ion battery
CN120164938A
Preparation method and application of silicon-based composite material
CN120914240A